Concise synthesis of (-)-deoxoprosopinine - Pandey, Satyendra Kumar; Kumar, Pradeep (Synlett, 2007)
A simple and highly efficient approach to (-)-deoxoprosopinine from racemic epoxide as a starting material is described employing a Jacobsen's hydrolytic kinetic resolution (HKR) and Sharpless asymmetric dihydroxylation (AD) as key steps.
Keywords: hydroboration-oxidation; Jacobsen's HKR; Piperidine alkaloids; sharpless AD; Total synthesis

Efficient and practical total synthesis of (+/-)-alpha-cuparenone - Chavan, Subhash P.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Synthesis-Stuttgart, 2007)
A one-pot cyclopentannulation approach as the key step for the total synthesis of (+/-)-alpha-cuparenone is described.
Keywords: Alkylation; annulation; hydroboration-oxidation; reduction

Efficient total synthesis of (-)-(3S,6R)-3,6-dihydroxy-10-methylundecanoic acid - Pandey, Satyendra Kumar; Kumar, Pradeep (European Journal of Organic Chemistry, 2007)
An efficient enantioselective synthesis of (-)-(3S,6R)-3,6-dihydroxy-10-methylundecanoic acid (1) from epichlorohydrin is described. The key steps include Jacobsen's HKR, Sharpless asymmetric dihydroxylation, regioselective opening of epoxide and cyclic sulfate. ((c) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007).
Keywords: cyclic sulfate; Dihydroxylation; Grignard reaction; hydroboration-oxidation; Jacobsen's hydrolytic kinetic resolution (HKR); regio selectivity